Production and use of anther culture derived DH-lines of oat - Kiviharju, Elina (MTT, 2004)
Application of DH-lines (doubled haploids) for cultivar breeding saves time and increases selection efficiency. DH-lines are also valuable material for genetic research. Benefits are based on the quick derivation of pure lines from heterogeneous crossing progeny, and the absence of dominance and heterozygosity of these lines. Oat DHs have been produced through anther culture and through wide hybridization (Rines 2003). However, unefficiency of the available methods has limited the use of haploids in oat breeding and research. Our aim was to increase oat DH production through anther culture to appropriate level. Culture medium and conditions were optimised on the basis of the previously reported protocol (Kiviharju et al. 2000). Also microspore culture was tested, but it was not successful. Significantly higher plant regeneration rates were got by improved culture medium. Rates up to 30 green regenerants per 100 isolated anthers were obtained, common numbers being around one or less per 100 cultured anthers. Response was genotype-dependent, but crossing progenies of the nonresponsive and well-responsive genotypes could be regenerated in several cases. In field conditions, some differences were found when anther culture derived DH-lines were compared with commercial seeds, but in general their quality was in line. Numerous oat DH-lines produced in the anther culture experiments were tested in field. In the present study we are using anther culture derived DHpopulation (150 DH-lines) for genetic mapping of oat quality characteristics. As a conclusion, production rates of anther culture derived DH-lines are approaching the numbers needed for practical applications, at least in some genotypes. Kiviharju, E. et al. 2000. Plant Cell Reports 19:674-679; Rines, H.W. 2003. In: Maluszynski, M. et al. (eds.). Doubled haploid production in crop plants. Kluwer. P. 155-159.
Keywords: Ka; androgenesis; anther culture; breeding; haploids; oats